DEVELOPMENT AND STANDARDIZATION OF AN ELECTRONIC TEST TO MEASURE MOTOR RESPONSE, SPEED, AND ACCELERATION IN THE SPIKE FOR BACK-ROW VOLLEYBALL PLAYERS - Amer Mishaal Faihan (Proximus Journal Publishing, 2025)
Based on the researcher's work in the sports field and specifically in volleyball testing, it was observed that the devices used for volleyball assessments do not measure the specific capacities required by back-row players—such as motor response, speed, and acceleration—using a single device without relying on highspeed cameras and motion analysis. Therefore, this study aimed to design an electronic device to measure motor response, acceleration, and speed during the performance of the spike skill among volleyball players. To properly address the research problem, the descriptive approach was used, which was deemed the most suitable methodology for this study. The research sample was selected from students of The College of Physical Education and Sports Sciences, comprising 100 fourth-year students. The researcher developed an electronic device capable of measuring all the investigated capacities, established its scientific foundations, standardized it, and derived its normative criteria.
Keywords: response; acceleration; speed; time